2020
DOI: 10.1111/psyg.12610
|View full text |Cite
|
Sign up to set email alerts
|

The effect of circadian preferences on insomnia severity and depressive symptoms via sleep hygiene in older adults with depression and healthy controls

Abstract: Background: The elderly population is increasing globally. Thus, researches focus on the causes and treatment of insomnia, a noteworthy ageing problem. This study aims to investigate the relationship between chronotype and insomnia and whether sleep hygiene mediates this relationship in older adults with depression (OAD). Methods: We assessed subjective insomnia severity, sleep hygiene, chronotype, depressive symptoms, and anxiety symptoms of 82 OAD and 70 healthy controls using the Sleep Hygiene Index (SHI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Following article screening, a total of 51 studies were entered into the initial random effects model. Outlier analyses identified a total of ten studies 49 58 and these were subsequently excluded from the analysis (See Supplemental S2 for details of these studies including the 95% CI for each excluded effect size). Heterogeneity was reduced after excluding these studies (prior to exclusion I 2 = 77.9%, Q(52) = 235.11, p < 0.001, after exclusion I 2 = 60.2%, Q(42) = 105.5, p < 0.001) but remained substantial and significant.…”
Section: Resultsmentioning
confidence: 99%
“…Following article screening, a total of 51 studies were entered into the initial random effects model. Outlier analyses identified a total of ten studies 49 58 and these were subsequently excluded from the analysis (See Supplemental S2 for details of these studies including the 95% CI for each excluded effect size). Heterogeneity was reduced after excluding these studies (prior to exclusion I 2 = 77.9%, Q(52) = 235.11, p < 0.001, after exclusion I 2 = 60.2%, Q(42) = 105.5, p < 0.001) but remained substantial and significant.…”
Section: Resultsmentioning
confidence: 99%
“…A large body of evidence demonstrated that poor sleep quality or sleep disorders mediate the association between evening chronotype and depressive symptoms in healthy subjects and patients with mood disorders ( Van den Berg et al, 2018 ; Caruso et al, 2020 ; Li et al, 2020 ; Tian et al, 2020 ; Uzer and Yucens, 2020b ; Lin et al, 2021 ; Zhou et al, 2021 ) or other adverse outcomes ( Cox and Olatunji, 2019 ; Kandeger et al, 2019 ; Najem et al, 2020 ; Bradford et al, 2021 ). A study of older adults with depression indicated that the relationship between evening chronotype and depression is fully mediated by insomnia severity ( Uzer and Yucens, 2020b ). Clinical evaluation of patients with BD indicated that poor sleep quality mediated the association between evening chronotype and residual depressive symptoms ( Caruso et al, 2020 ).…”
Section: The Differences Between Chronotypes and The Association With...mentioning
confidence: 99%
“…Consistent with previous research, people with eveningness-preference have poorer sleep hygiene practices, meaning they tend to engage in environmental and behavioral habits that lower sleep quality (e.g., drinking coffee or alcohol before sleep, irregular sleep time, improper temperature or light in the bedroom, etc. ), and thus have more insomnia symptoms ( 45 ). Prior studies have also found that patients with eveningness preference showed poorer response to classic insomnia treatments, thereby suggesting that chronotype might be related to the development of psychiatric diseases through distinct mechanisms ( 46 48 ).…”
Section: Discussionmentioning
confidence: 99%